Does whey protein supplementation affect blood pressure in hypoalbuminemic peritoneal dialysis patients? - Hassan K; Hassan F (Dove Medical Press, 2017)
Kamal Hassan,1,2 Fadi Hassan3 1Faculty of Medicine in the Galilee, Bar-Ilan University, Safed, 2Department of Nephrology and Hypertension, Peritoneal Dialysis Unit, 3Department of Internal Medicine E, Galilee Medical Center, Nahariya, Israel Objective: Hypertension and hypoalbuminemia are common risk factors for cardiovascular complications in peritoneal dialysis (PD) patients. Data are limited regarding the effects of whey protein consumption on blood pressure in this population. The aim of the present study was to examine if whey protein supplementation for 12 weeks to hypoalbuminemic PD patients affects their blood pressure.Patients and methods: This prospective randomized study included 36 stable PD patients with serum albumin levels <3.8 g/dL. During 12 weeks, 18 patients were instructed to consume 1.2 g/kg/day of protein and an additional whey protein supplement at a dose of 25% of the instructed daily protein (whey protein group). Eighteen patients were instructed to consume protein in the amount of 1.2 g/kg/day and an additional 25%, without whey protein supplementation (control group). Results: Compared to the control group, in the whey protein group, serum albumin levels, oncotic pressure, and dialysate ultrafiltration significantly increased (3.55±0.14 to 4.08±0.15 g/dL, P<0.001; 21.81±2.03 to 24.06±1.54 mmHg, P<0.001; 927.8±120.3 to 1,125.0±125.1 mL/day, P<0.001; respectively) and were significantly higher after 12 weeks (4.08±0.15 vs 3.41±0.49 g/dL, P<0.001; 24.06±1.54 vs 22.71±1.77 mmHg, P=0.010; 1,125.0±125.1 vs 930.6±352.8 mL/day, P=0.017; respectively) in the whey protein group compared to the control group. Fluid overload, the extracellular to intracellular ratio and mean arterial pressure (MAP) significantly decreased (2.46±1.08 to 1.52±0.33, P<0.001; 1.080±0.142 to 0.954±0.124, P<0.001; 102.6±3.80 to 99.83±3.85, P=0.018; respectively) and were significantly lower in the whey protein group after 12 weeks (1.52±0.33 vs 2.23±0.73, P<0.001, 0.954±0.124 vs 1.048±0.111, P=0.002; 99.83±3.85 vs 102.8±3.93, P=0.018; respectively).Conclusion: Whey protein supplementation for 12 weeks decreased MAP in hypoalbuminemic PD patients. Keywords: blood pressure, hydration status, oncotic pressure, peritoneal dialysis, whey protein